Comparación de las características clínicas de pacientes con infarto agudo de miocardio según género - Castro Leyva, Fernando Enrique (2015)
Objective: Compare clinical characteristics by gender in hospitalized patients with acute myocardial infarction in Regional Hospital of Trujillo and Belen Hospital of Trujillo during the period 2009-2013. Material and Methods: This is a descriptive study that included 174 clinical histories pf patients with acute myocardial infarction attended on Regional Hospital of Trujillo and Belen Hospital of Trujillo during the period January 2009 - December 2013. Clinical characteristics were determined and a comparison between male and female groups. Results and Conclusions: From the review of 174 clinical histories, most of them were man. The average age of presentation was higher for women. Hypertension and smoking predominate in man. Killip score type I was associated to male gender. The most frequent localization was anterior, followed by anteroseptal and inferior, without gender differences. The elevation of the ST segment was more frequent, without gender differences. Complications were all intrahospital pneumonias and no relation was found to gender.